Ageing and Growth Records of Anabas testudineus (Bloch) (Anabantidae : Perciformes) - Nargis, A (Bangladesh Journal of Scientific and Industrial Research, 2010)
Observations on otoliths of 115 males and 67 females of 1-11 age group have shown that the transparent (hyaline) and opaque rings are formed annually on the Anabas testudineus otolith. The validity of the otolith study has been confirmed by obtaining high co- efficient of correlation (0.94 and 0.93) between total length (TL) and otolith (OR) of 337 males and 387 females of A. testudineus. But the significant differences (t=15.80, D. F=722; P < 0.001) between the sexes have indicated the use of length intercept separately for back calculation for males and females. Growth rate for females (k=0.174, L=237.12) was found to grow faster than that of males (k=0.182, L=18). From the age length distribution it is inferred that on an average, lengths of 105.30±3.98, 122.56±5.22, 143.24 ±5.66 for males and 106.70±5.17, 127.81±5.20 and 145.59±5.42 for females are attained by the species in the respective ages of 3 years of their life spans . Keywords: Growth rate; Stractures of fish; Rapid metabolism DOI: 10.3329/bjsir.v45i3.6539 Bangladesh J. Sci. Ind. Res. 45(3), 283-287, 2010